Religious Coping and Locus of Control in Normal Pregnancy: Moderating Effects Between Pregnancy Worries and Mental Health - Puente, Cecilia Peñacoba (Journal of religion and health, 2015)
Most studies about coping in pregnancy focus on risk pregnancies where it has generally been found that the use of religious coping has a positive effect, although to our knowledge there are no studies that associate religious coping to locus of control. We analyzed, in a sample of 285 Spanish women with normal pregnancies, the effect of both variables on psychiatric symptoms and on the relationship between psychiatric symptoms and pregnancy worries. The results show no association between locus of control and religious coping. Locus of control has a significant influence on the pregnant women’s mental health, while religious coping just adds an additional influence.